Methane Number Improvement of Gas from LNG Regasification Unit - Tjojudo Danianto Hendragiri; Kartohardjono Sutrasno (E3S Web of Conferences, 2018)
Methane Number (MN) is one of quality requirement of gas as fuel for gas engine, which indicates fuel capability to avoid knocking in the engine. Higher MN provides better quality of gas for gas engine. Natural gas with higher methane (CH4) and fewer higher hydrocarbon, tends to have higher MN score. This study aims to obtain heating methods of LNG to produce vapor that has appropriate MN as a fuel gas supply to gas engine. The simulation for LNG regasification prepared is an approach to the design of the existing regasification facility of the power plant in Bali. The temperature ranges for LNG heating simulation were obtained based on saturated temperatures of LNG phase envelopes. In the simulation. to obtain a certain MN value can be conducted by adjusting the temperatures at two different values i.e. above -110 ° and below - 80 °. To produce LNG vapor that has MN of 80 either through higher temperature of heating (HT heating) or lower temperature of heating (LT heating) requires more energy than direct heating without MN improvement. Heat loading for LT heating is higher than HT heating due to more temperature defference between LT and heating fluid temperatures. The ability of engine to produce power decreased with decreasing fuel gas MN. The power increment increases for lower MN gas if MN improvement is conducted.